Current and potential threat of psyllids (Hemiptera: Psylloidea) on eucalypts. Issue 3 (16th November 2020) - Makunde, Privilege T; Slippers, Bernard; Burckhardt, Daniel; de Queiroz, Dalva L; Lawson, Simon A; Hurley, Brett P
Abstract : The introduction of Australian psyllids to non-native ranges across the globe is continually increasing. This is due to an increase in global trade and human movement, exacerbated by climate change. Several psyllids have been recorded as pests of eucalypts in the native range of these trees. With the current trend of eucalypt pest introductions, there is a concern that many more eucalypt-feeding psyllids in Australia will in time be introduced and become pests in eucalypt-growing regions of other continents. Here we examine the current and potential threat of psyllids on eucalypts. Specifically, we consider the diversity of eucalypt psyllids in their native range and those eucalypt psyllids that have been introduced outside Australia and become pests in their new ranges. In addition, the potential pathways and characteristics of these invasive psyllids are discussed.